Lactiplantibacillus plantarum FRT4 protects against fatty liver hemorrhage syndrome: regulating gut microbiota and FoxO/TLR-4/NF-κB signaling pathway in laying hens - Daojie Li; Kun Meng; Guohua Liu; Zhiguo Wen; Yunsheng Han; Weiwei Liu; Xin Xu; Liye Song; Hongying Cai; Peilong Yang (Microbiome)
Abstract Background Fatty liver hemorrhage syndrome (FLHS) has become one of the major factors leading to the death of laying hen in caged egg production. FLHS is commonly associated with lipid peroxidation, hepatocyte injury, decreased antioxidant capacity, and inflammation. However, there are limited evidences regarding the preventive effect of Lactiplantibacillus plantarum on FLHS in laying hens and its mechanisms. Our previous results showed that Lp. plantarum FRT4 alleviated FLHS by regulating lipid metabolism, but did not focus on its antioxidant and anti-inflammatory functions and mechanisms. Therefore, this study aimed to investigate the preventive mechanisms of Lp. plantarum FRT4 in alleviating FLHS, with a focus on its role in antioxidant activity and inflammation regulation. Results Supplementation with Lp. plantarum FRT4 enhanced the levels of T-AOC, T-SOD, and GSH-Px, while reducing the levels of TNF-α, IL-1β, IL-8, and NLRP3 in the liver and ovary of laying hens. Additionally, Lp. plantarum FRT4 upregulated the mRNA expressions of SOD1, SOD2, CAT, and GPX1, downregulated the mRNA expressions of pro-inflammatory factors IL-1β, IL-6, and NLRP3, and upregulated the mRNA expressions of anti-inflammatory factors IL-4 and IL-10. Lp. plantarum FRT4 improved the structure and metabolic functions of gut microbiota, and regulated the relative abundances of dominant phyla (Bacteroidetes, Firmicute, and Proteobacteria) and genera (Prevotella and Alistipes). Additionally, it influenced key KEGG pathways, including tryptophan metabolism, amino sugar and nucleotide sugar metabolism, insulin signaling pathway, FoxO signaling pathway. Spearman analysis revealed that the abundance of microbiota at different taxonomic levels was closely related to antioxidant enzymes and inflammatory factors. Furthermore, Lp. plantarum FRT4 modulated the mRNA expressions of related factors in the FoxO/TLR-4/NF-κB signaling pathway by regulating gut microbiota. Moreover, the levels of E2, FSH, and VTG were significantly increased in the ovary after Lp. plantarum FRT4 intervention. Conclusions Lp. plantarum FRT4 effectively ameliorates FLHS in laying hens. This efficacy is attributed to its antioxidant and anti-inflammatory properties, which are mediated by modulating the structure and function of gut microbiota, and further intervening in the FoxO/TLR-4/NF-κB signaling pathway. These actions enhance hepatic and ovarian function and increase estrogen levels. Video Abstract